Basics of Ankle Arthroscopy Part 7: Achilles Tendoscopy: Surface Anatomy, Portal Placement, and Diagnostic Evaluation - James J. Butler, M.B., B.Ch.; Mackeznie Roof, M.D.; Nathan Lorentz, M.D.; Alexander J. Egol, M.D.; Sebastian Krebsbach, B.S.; John G. Kennedy, M.D., M.Ch., M.MSc., F.F.S.E.M., F.R.C.S. (Orth) (Arthroscopy Techniques)
Achilles tendoscopy is an important diagnostic and therapeutic tool in the treatment of pathologies of the Achilles tendon. In this article, the basics of Achilles tendoscopy are reviewed, including the relevant surface anatomy, portal placement, and diagnostic tendoscopic techniques. We also compare the benefits and limitations associated with performing Achilles tendoscopy with a 1.9-mm 0° needle endoscope compared to utilizing a 2.7-mm or 4.0-mm 30° endoscope. Level of Evidence: Level V, technique.